Odpowiedzi

2010-03-07T11:29:58+01:00
a)x=34+(-35)
x=-1

4x-3x=-5
1x=-5
x=-5
b)2x-x=46-64
x=-110

3x+2x=2-4
5x=-2
x=-0,4
c)-2x+x=-1/4+1/2
-x=-1/4
x=1/4

-3x+4x=-1 3/4-3 1/4
x=2 3/4
1 3 1
Najlepsza Odpowiedź!
2010-03-07T11:40:59+01:00
A)x-34=-35
x=34-35
x=-1

4x=3x-5
4x-3x=-5
x=-5

b)64+2x=46+x
2x-x=-64+46
x=-18

3-x=-2x
-x+2x=-3
x=-3

4+3x=2+2x
3x-2x=-4+2
x=-2

c)x+¼=½+2x|*4
4*x+4*¼=4*½+4*2x
4x+1=2+8x
4x-8x=-1+2
-4x=1|:(-4)
x=-¼

3x+1/7=x-1|*7
7*3x+7*1/7=7*x-7*1
21x+1=7x-7
21x-7x=-1-7
14x=-8|:14
x=-8/14=-4/7

1¾-3x=-3¼-4x |*4
4*7/4-4*3x=4*-13/4-4*4x
7-12x=-13-16x
-12x+16x=-7-13
4x=-20|:4
x=-5






1 3 1